The Tribomechadynamics Research Challenge: Confronting blind predictions for the linear and nonlinear dynamics of a thin-walled jointed structure with measurement results - Krack, Malte; Brake, Matthew R.W.; Schwingshackl, Christoph; Gross, Johann; Hippold, Patrick; Lasen, Matias; Dini, Daniele; Salles, Loic; Allen, Matthew S.; Shetty, Drithi; Payne, Courtney A.; Willner, Kai; et al. (Mechanical Systems and Signal Processing, 2025)
The present article summarizes the submissions to the Tribomechadynamics Research Challenge announced in 2021. The task was a blind prediction of the vibration behavior of a system comprising a thin plate clamped on two sides via bolted joints. Both geometric and frictional contact nonlinearities are expected to be relevant. Provided were the CAD models and technical drawings of all parts as well as assembly instructions. The main objective was to predict the frequency and damping ratio of the lowest-frequency mode as function of the amplitude. Many different prediction approaches were pursued, ranging from well-known methods to very recently developed ones. After the submission deadline, the system has been fabricated and tested. The aim of this article is to evaluate the current state of the art in modeling and vibration prediction, and to provide directions for future methodological advancements.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Friction damping; Geometric nonlinearity; Jointed structures; Nonlinear dynamics; Nonlinear modal analysis